A framework for Comminution Circuits Design evaluation using grey compromise programming - Stanujkic, Dragisa; Stojanovic, Sanja; Jovanovic, Rodoljub; Magdalinovic, Nedeljko (Journal of Business Economics and Management, 2013)
Comminution process, particularly grinding, is very important in the mineral processing industry. Some characteristics of ore particles, which occur as a product of grinding process, have a significant impact on the effects of further ore processing. At the same time, this process requires a significant amount of energy and also significantly affects the overall processing costs. Therefore, in this paper, we propose new multiple criteria decision making model based on grey compromise programming for adequate comminution circuit design selection. Although it is based on a simple procedure, we consider that the proposed model is efficient and flexible, and that it also represents the basis for forming more sophisticated models for comminution circuit design selection, as in addition, many other decision making problems in business environment, which is characterized by predictions and uncertainty.